2018
DOI: 10.21926/obm.genet.1804057
|View full text |Cite
|
Sign up to set email alerts
|

Pneumocystis as a Co-Factor in Pulmonary Diseases

Abstract: Pneumocystis causes life-threatening pneumonia in immunocompromised populations. More recently it has been implicated as a co-factor in a number of chronic lung diseases including chronic obstructive pulmonary disease (COPD), severe asthma, and cystic fibrosis (CF). In this review, we will examine the current literature regarding Pneumocystis and lung diseases in the HIV-infected patients and non-HIV immunocompromised populations, and the barriers to prophylaxis and treatment in these patients. Trimethoprim su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 94 publications
(169 reference statements)
3
1
0
Order By: Relevance
“…Moreover, in several aspects, the presented data in this work showed that the presence of Pneumocystis in the airways worsens features of COPD. The increment of inflammation and emphysema lesions is similar with previous reports described in COPD patients, where Pneumocystis colonization increases the severity of COPD disease in HIV and non-HIV patients [34,42], supporting the hypothesis that Pneumocystis is a co-factor in chronic inflammatory lung diseases [37]. Interestingly, a recent work documented the role of Pneumocystis in the development of COPD disease in immunosuppressed animals [43], indicating a novel function of this fungus in the origin of the COPD disease.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Moreover, in several aspects, the presented data in this work showed that the presence of Pneumocystis in the airways worsens features of COPD. The increment of inflammation and emphysema lesions is similar with previous reports described in COPD patients, where Pneumocystis colonization increases the severity of COPD disease in HIV and non-HIV patients [34,42], supporting the hypothesis that Pneumocystis is a co-factor in chronic inflammatory lung diseases [37]. Interestingly, a recent work documented the role of Pneumocystis in the development of COPD disease in immunosuppressed animals [43], indicating a novel function of this fungus in the origin of the COPD disease.…”
Section: Discussionsupporting
confidence: 88%
“…This evidence supports the hypothesis that mild infection by Pneumocystis potentiates inflammation in respiratory diseases such as COPD directly or as a co-factor [37]. However, the mechanisms underlying this role are still unknown [37]. Therefore, we aimed to determine the role of Pneumocystis in the potentiation of inflammation and mucus secretion in a COPD host.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…Recently, the association between COPD and Pneumocystis infection in regard to disease severity has been demonstrated using an elastase-induced COPD rat model showing an increase in inflammation and mucus-related markers [ 35 ]. This new evidence supports the hypothesis that a mild Pneumocystis infection may amplify inflammation or other pathophysiological features, such as fibrosis in respiratory diseases like COPD, either directly or as a co-factor [ 36 ]. However, the mechanisms underlying this role remain elusive and it is necessary to explore other pathways, such as TGFβ1 or IL1β.…”
Section: Introductionsupporting
confidence: 82%